Visual acuity, literacy, and unintentional misuse of nonprescription medications. (1st May 2018) - Mullen, Rebecca J.; Curtis, Laura M.; O'Conor, Rachel; Serper, Marina; McCarthy, Danielle; Bailey, Stacy C.; Parker, Ruth M.; Wolf, Michael S.
Abstract : Purpose: Results of a study of associations between visual acuity and the risk of misuse of nonprescription acetaminophen products in a sample of community-dwelling adults are reported. Methods: In a study involving English-speaking adults at 4 primary care clinics, the potential for misuse of nonprescription acetaminophen products was measured via a functional assessment of product self-dosing and by testing patients' understanding of the risks of concomitant use (i.e., taking 2 products at the same time when contraindicated). Vision was assessed using the Rosenbaum vision chart and dichotomized as normal (visual acuity of 20/20–20/25) or low (acuity of 20/30–20/100). Bivariable and multivariable analyses were performed to determine the impact of visual acuity on medication misuse outcomes. Results: Among the study participants ( n = 500), 39% had limited literacy, and 54% were categorized as having low vision. After controlling for age, race, and prior acetaminophen use, low vision was independently associated with an increased risk of self-dosing errors (odds ratio [OR], 1.67; 95% confidence interval [CI], 1.25–2.21; p < 0.001) and misunderstanding of concomitant-use risks (OR, 1.41; 95% CI, 1.00–2.00; p = 0.05). Limited literacy was an independent risk factor for incorrect dosing (OR, 1.71; 95% CI, 1.25–2.35; p = 0.001) and unawareness of concomitant use instructions (OR, 4.14; 95% CI, 2.80–6.12; p < 0.001). Conclusion: Misunderstanding of nonprescription acetaminophen product information was common among study participants and independently associated with both impaired visual acuity and low literacy skills.